ANALISIS SEMIOTIKA RIFFATERRE PADA CERPEN SERIBU KUNANG-KUNANG DI MANHATTAN KARYA UMAR KAYAM - Nehla Rohali; Liza Septa Wilyanti (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2023)
This study aims to find meaning distortions, shifts in meaning, matrices, models, variants, and hypograms of Umar Kayam's short story Seribu Fireflies in Manhattan. The research method used is descriptive qualitative. The data collection method used is the hermeneutic method which adheres to Riffaterre's semiotic theory. From the research that has been done, it is found that there are four possible stories and two types of indirect expressions in this short story in the form of meaning distortion which includes metaphor and metonymy, and replacement of meaning which includes contradiction, ambiguity, and nonsense. The matrix of this short story is a two-way conversation between Jane and Marno who leads the whole story with a romantic but firm model by Umar Kayaman. The conclusion of the research that can be drawn is that short stories can be categorized as contemporary literary works because of the complexity of the language style, the indirect expression in this short story is in the form of deviation and substitution of meaning, and the matrix of this short story is a two-way conversation between Jane and Marno who leads the whole story with a model that romantic but firm